2016
DOI: 10.1039/c6nj02089e
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexes bearing an NHC–calixarene unit: synthesis and application in click chemistry

Abstract: Novel N-heterocyclic carbene (NHC) copper complexes supported by calix[4]arene were synthesized and showed good catalytic activity when applied in click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The Cu I -catalyzed cycloaddition of azides and alkynes (CuAAC) affording triazoles is undoubtedly the most common example of a Click-reaction [129]. In this scenario, copper complexes supported by NHC-functionalized calix [4]arene ligands (144-145, Figure 41) have recently been studied (Scheme 20) [130]. High functional group tolerance with respect to both azide and alkyne parts was observed.…”
Section: Cycloaddition Of Azides and Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu I -catalyzed cycloaddition of azides and alkynes (CuAAC) affording triazoles is undoubtedly the most common example of a Click-reaction [129]. In this scenario, copper complexes supported by NHC-functionalized calix [4]arene ligands (144-145, Figure 41) have recently been studied (Scheme 20) [130]. High functional group tolerance with respect to both azide and alkyne parts was observed.…”
Section: Cycloaddition Of Azides and Alkynesmentioning
confidence: 99%
“…Scheme 20. Selected results for the cycloaddition of azides and alkynes (CuAAC) catalyzed by 144[130].…”
mentioning
confidence: 99%
“…Azides 2a – 2g were prepared through an adapted Vogel's procedure . Their characterization was compared with data reported in literature …”
Section: Methodsmentioning
confidence: 99%
“…These complexes have been applied in reactions including: Suzuki cross-coupling reactions in aqueous solution (where traditional NHCs may yield poorly soluble complexes) [89], Heck reactions [86], and copper-catalysed azide-alkyne cycloadditions [90]. In a study of Suzuki-Miyaura coupling catalysed by a calix [6]arene complex containing three nickel centres it was shown that the best results were obtained using the complexes in which the nickel centres are closest to the calix [6]arene rim [91].…”
Section: Calixarenes and Pillararenesmentioning
confidence: 99%